Investing in Electricity, Growth, and Debt Sustainability : The Case of Lesotho - Andreolli, Michele (IMF Working Papers; Working Paper ;, 2016)
This paper analyses a large public investment in a construction of a hydropower plant in Lesotho and its implications on the growth and debt sustainability. The paper employs an open economy dynamic general equilibrium model to assess the benefits of a large public investment through growth-enhancing increase in domestic energy supply and receipts from selling electricity abroad to ease the fiscal burden, which is often associated with big investment projects. During the transition (construction stage), various financing options are explored: increase in the public debt, increase in domestic revenue (fiscal adjustment), and combination. The calibration matches Lesotho's data and it captures the project's main challenges regarding the project costs. Moreover,the key remaining issue is the agreement with South Africa to purchase sufficient amount of electricity to allow the potential plant to run at a high capacity. We find that, the project can lead to sizable macroeconomic benefits as long as costs are relatively low and demand from South Africa is sufficiently high. However, the risks for the viability of the project are high, if these assumptions are violated.